FINANCIAL SECURITY OF THE STATE: ESSENCE AND APPROACHES - Tsapova Olga Alexandrovna, (Academic Journal of Physical and Chemical Sciences, 2020)
The role of public finance in modern conditions is that they should influence the process of social reproduction, acceleration of economic growth, structural reorganization of the economy, acceleration of scientific and technological progress. The expansion of public investment provides an increase in demand for equipment, which in turn makes it more effective for industrial production, employment, and revitalization of the economic environment. At the expense of the state budget, demand is maintained, social events and programs are financed, etc. The impact on the economy, although controversial, is also exerted by the costs associated with ensuring the state’s defense capability. On the one hand, these costs give a certain impetus to the development of industry, on the other hand, a long arms race leads to the depletion of the economy, intraeconomic imbalances, a change in the structure of production and other negative consequences